1954
DOI: 10.1021/ja01639a059
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Glutamic Acid with 1-Hydroxy-2-aminobutane1,2

Abstract: Unsubstituted DL-glutamic acid has been resolved by use of an optical isomer of the readily available l-hydroxy-2-aminobutane. The amine used was obtained by resolution with either tartaric acid or glutamic acid. Attempts to extend this method to aspartic acid resulted in partial resolution only. Formyl-DL-phenylalanine, however, was resolved to give the pure isomers readily. Mutual solubilizing effects are described for diastereomers of the hydroxybutaneammonium hydrogen glutamate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0
2

Year Published

1960
1960
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 8 publications
2
1
0
2
Order By: Relevance
“…Ternary Equilibrium Data for l( + )-2-Amino-l-butanol-L( + )-hemitartarate (I)- "mf = mass fraction (-)-2-amino-l-butanol-L(+)-hemitartarate (II). This observation is in agreement with the trend previously reported by Radke et al (1954) and by many patentees.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Ternary Equilibrium Data for l( + )-2-Amino-l-butanol-L( + )-hemitartarate (I)- "mf = mass fraction (-)-2-amino-l-butanol-L(+)-hemitartarate (II). This observation is in agreement with the trend previously reported by Radke et al (1954) and by many patentees.…”
Section: Resultssupporting
confidence: 94%
“…The solvents employed are water and different alkanols. The information available on the process is, however, very limited (Radke et al, 1954;Pitre and Grabitz, 1969) and is found mostly in the patent literature (Zoja, 1971;Seres and Daroczi, 1970;Ichikawa et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…(DL) = (D) + 0) Adl Ad Kl Solving eq 7 for ADL gives eq 8 which describes the relationship of the dissociation constant of the racemic compound to its enantiomers for competitive enzyme inhibitors. § ^DL "" 2 KDKL KO+KL (8) The dissociation constants for the racemic compounds were calculated from eq 8 using the experimental data presented in Table I. In all cases, the caled A,'s for the racemic compound agree well with the found values (see Table I).…”
supporting
confidence: 56%
“…(R)-( -)-2-Anziizobutanol-(l) wird analog aus dem Salz des (I? )-( -)-2-Aniino-t)utanols-(l) mit l a erhalten: [a],:: = -10,lO" ( d = 0,940); Litcratunvert[6]:[cr],;: = -9,92" (d = 0,939). Ofitische Spaltiwzg voiz (R) ( S ) -( / -l~h e n~~l -d t h y I ) -a r n i n init I b und I n .…”
unclassified
“…Das einfache und effektive chromatographische Verfahren hat sich bei der Synirhese von [S a-14C]-Biopterin bewahrt [5]. Es erlaubte erstmals die Reindarstellung und damit die Charakterisierung des Neopterins und seiner drei optischen Isomeren [6] und spater auch der drei optischen Isomeren des Biopterins [7]. Es wurde auch bei der Darstellung von Aminobiopterin und Aminoneopterin erfolgreich angewandt [8].…”
unclassified